2010
DOI: 10.1200/jco.2009.25.7246
|View full text |Cite
|
Sign up to set email alerts
|

Significant Effect of Polymorphisms in CYP2D6 and ABCC2 on Clinical Outcomes of Adjuvant Tamoxifen Therapy for Breast Cancer Patients

Abstract: A B S T R A C T PurposeThe clinical efficacy of tamoxifen is suspected to be influenced by the activity of drug-metabolizing enzymes and transporters involved in the formation, metabolism, and elimination of its active forms. We investigated relationships of polymorphisms in transporter genes and CYP2D6 to clinical outcome of patients receiving tamoxifen. Patients and MethodsWe studied 282 patients with hormone receptor-positive, invasive breast cancer receiving tamoxifen monotherapy, including 67 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
204
4
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(226 citation statements)
references
References 28 publications
(11 reference statements)
15
204
4
3
Order By: Relevance
“…The prospective studies [20,32], however, were also retrospective in nature since CYP2D6 genotyping has been performed after the relapse had eventuated. Nonparametric analyses and substantial overlaps in the patients' data were also reported in the following studies [10,[33][34][35]. Nevertheless, two prospective yet small studies [36,38] and two large trials (n>1300) [35,40] have reported statistically strong correlation between CYP2D6 genotype and clinical outcome in patients with breast cancer taking tamoxifen.…”
Section: Clinical Validitymentioning
confidence: 99%
See 4 more Smart Citations
“…The prospective studies [20,32], however, were also retrospective in nature since CYP2D6 genotyping has been performed after the relapse had eventuated. Nonparametric analyses and substantial overlaps in the patients' data were also reported in the following studies [10,[33][34][35]. Nevertheless, two prospective yet small studies [36,38] and two large trials (n>1300) [35,40] have reported statistically strong correlation between CYP2D6 genotype and clinical outcome in patients with breast cancer taking tamoxifen.…”
Section: Clinical Validitymentioning
confidence: 99%
“…*4/*10/*41) are robust predictors of tamoxifen's antitumoral efficacy [10,20,34,37]. Moreover, findings from a prospective study found that CYP2D6 polymorphisms were strongly associated with Ki-67 response, implying that CYP2D6 genetic variation is an important predictor for efficacy of tamoxifen in women with breast cancer [38].…”
Section: Clinical Validitymentioning
confidence: 99%
See 3 more Smart Citations